GE_GERICHTE P/6819/2018 vom 16. Mai 2018 - GE Cour de justice (2018)
APPROPRIATION ILLÉGITIME ; ABUS DE CONFIANCE ; SOUSTRACTION D'UNE CHOSE MOBILIÈRE ; LEASING ; DÉPENS ; PLAIGNANT | CPP.310; CPP.436; CPP.433.al2; CP.137; CP.138; CP.141